2010
DOI: 10.5424/fs/201019s-9290
|View full text |Cite
|
Sign up to set email alerts
|

Modelling bird species richness with neural networks for forest

Abstract: For preserving biodiversity of European-Mediterranean forest ecosystems in current and future scenarios of global change by means of sustainable forest management it is necessary to determine how environment and forest characteristics correlate with biodiversity. For this purpose, neural networks were used to model forest bird species richness as a function of environment and forest structure and composition at the 1 × 1 km scale in Catalonia (NE Spain). Univariate and multivariate models respectively allowed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…This type of result can be observed in other reports. Gil-Tena et al (2010) reported that all the variables show positive signs, but aspect diversity, temperature, public forest, and road and population density, display an inverse relationship.…”
Section: Discussionmentioning
confidence: 99%
“…This type of result can be observed in other reports. Gil-Tena et al (2010) reported that all the variables show positive signs, but aspect diversity, temperature, public forest, and road and population density, display an inverse relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Topography is a well-known driver of species richness in the tropical forests [ 95 , 96 ]. A previous study also discovered that topographic variables influence avian species richness at an intermediate scale of 1 km 2 [ 27 ]. Neotropical research revealed that avian richness is extremely sensitive to variations in elevation and topography [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even at the resolution of 1 degree (111.32 km), topography and temperature are more important determinants of global scale avian diversity [ 25 ]. While habitat characteristics influence species richness at finer scales [ 26 ], the role of bioclimatic and topographic variables cannot be eliminated [ 27 ]. In addition, species richness is influenced by anthropogenic factors such as distance from roads and forest management regimes [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Special Issue is structured around five review articles focused on five questions that were chosen based on of their intrinsic scientific importance as well as their significance for decision-making in forest management: (i) Models for supporting forest management in a changing environment (Fontes et al, 2010); (ii) Recent approaches to model the risk of storm and fire to European forests and their integration into simulation and decision support tools (Hanewinkel et al, 2010); (iii) Simulating wood quality in forest management models (Mäkelä et al, 2010); (iv) Modelling non-wood forest products in Europe: a review (Calama et al, 2010); and lastly, (v) Simulation tools for decision support to adaptive forest management in Europe (Muys et al, 2010). In addition, the special issue is complemented with two original papers dealing with forest genetics modeling (Kramer and Van der Werf, 2010) and an example of modeling forest birds using neural networks (Gil-Tena et al, 2010).…”
Section: Introductionmentioning
confidence: 99%